Paradoxical recovery in a bilingual patient with aphasia after right capsuloputaminal infarction. Issue 1 (15th December 2006) - García-Caballero, A; García-Lado, I; González-Hermida, J; Area, R; Recimil, M J; Juncos Rabadán, O; Lamas, S; Ozaita, G; Jorge, F J
Abstract : We report the case of a bilingual dextral patient, who presented with an uncommon pattern of aphasic deficit following a right capsulo-putaminal infarction. In this patient, the linguistic deficit concerned the use of her mother tongue (Galician, L1) much more than the lesser practised second language (Spanish, L2). Our patient presented spontaneous fluent speech in L2 but not in L1, automatic translation into L2, and impaired repetition in L1, whereas comprehension was spared in both L1 and L2. Reading and writing were less valuable due to educational interference (reduced schooling). Spontaneous speech 16 months after the stroke showed the stability of the impairment. This is the first reporting of a crossed subcortical aphasia in a bilingual patient.